If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -14 = 10 + -1x Reorder the terms: -14 + 5x = 10 + -1x Solving -14 + 5x = 10 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -14 + 5x + x = 10 + -1x + x Combine like terms: 5x + x = 6x -14 + 6x = 10 + -1x + x Combine like terms: -1x + x = 0 -14 + 6x = 10 + 0 -14 + 6x = 10 Add '14' to each side of the equation. -14 + 14 + 6x = 10 + 14 Combine like terms: -14 + 14 = 0 0 + 6x = 10 + 14 6x = 10 + 14 Combine like terms: 10 + 14 = 24 6x = 24 Divide each side by '6'. x = 4 Simplifying x = 4
| 0=6-4x-2x^2 | | 0=6-2x-3x^2 | | 2x-10=y | | log(x)32=5 | | 188=(6-x)2 | | -4t^2+3t+325=0 | | xy-3x=2y-1 | | -x+8=10x+89 | | 9x^2+3x^3=0 | | y=1x+140 | | 6x+18=4x+124 | | -16+8y=2y+20 | | 2x+2x^2+2y^2-30=0 | | 5x+25=5x+15 | | 100=10ln(x+2)+50 | | 128+16s-4s^2= | | (3x-4)+(3x+10)-(2x-4)=6 | | 1x+4y=52263 | | p=3(1+3x) | | 6-5/4x1 | | 581+840y+295y^2=0 | | -2(1-5x)=-(x+1) | | 360+96k=0 | | -2(x+4)+5= | | x+2=7y | | 3x^2-12=0 | | 96=94p | | x-5/3=6 | | 50.50+18n= | | 2c+8=81 | | [2x+9]-10=5 | | -12-(x-3)=4x+5 |